2022
DOI: 10.1038/s41380-022-01675-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in plasma p-tau181 associations with Alzheimer’s disease biomarkers, cognitive decline, and clinical progression

Abstract: Studies have shown that women on the Alzheimer’s disease (AD) continuum have more pathological tau in the brain and cerebrospinal fluid (CSF), than men. Some studies have found that higher levels of tau biomarkers are more strongly associated with clinical AD, cognitive decline and neurodegeneration in women than in men. Despite major developments in the use of plasma tau phosphorylated at threonine 181 (p-tau181) as an AD biomarker, it is unknown whether these sex differences apply to plasma p-tau181. In 1060… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…Notably, females showed higher GFAP and NfL levels, also corroborating recent findings 40 . Lower plasma p‐tau181 in females has also been reported 41 . While Aβ42/40 ratio was not affected by education, NfL, GFAP, and p‐tau181 were lower in the more‐educated groups.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, females showed higher GFAP and NfL levels, also corroborating recent findings 40 . Lower plasma p‐tau181 in females has also been reported 41 . While Aβ42/40 ratio was not affected by education, NfL, GFAP, and p‐tau181 were lower in the more‐educated groups.…”
Section: Discussionsupporting
confidence: 87%
“…A secondary analysis from the ADNI study shown that sex may impact the clinical interpretation of plasma p-tau181 concentrations ( 25 ). In women, high plasma p-tau levels were associated with worse phenotypic markers (i.e., greater cortical Aβ deposition, higher CSF p-tau181 levels, lower brain glucose metabolism) compared with men.…”
Section: State-of-scientific Development Of Blood-based Markersmentioning
confidence: 99%
“…Findings from community and population-based AD studies found that levels of plasma P-tau217 did not differ between males and females, 2,5 while a recent study showed that higher plasma P-tau181 was associated with greater amyloid and entorhinal cortex tau accumulation, lower brain glucose metabolism, and faster cognitive decline in females, relative to males. 30 Research examining the effect of sex/gender on plasma biomarkers of neurodegeneration in AD cohort studies have also yielded mixed findings. Several studies have not found sex/gender differences in plasma NfL 5,12,31 or total tau.…”
Section: Introductionmentioning
confidence: 99%